Production of activated carbon as catalyst support by microwave pyrolysis of palm kernel shell: a comparative study of chemical versus physical activation - Cheng, C. K.; Osazuwa, Osarieme U.; Liew, Rock Keey; Chong, Min Yee; Nam, Wai Lun; Phang, Xue Yee; Su, Man Huan; Chong, Cheng Tung; Lam, Su Shiung (Springer, 2018)
Palm kernel shell (PKS), representing an abundantly available oil palm waste in Malaysia, was transformed into activated carbon by microwave vacuum pyrolysis. PKS was first carbonized to produce biochar, followed by an activation process with chemical or water to produce chemically and physically activated carbon, respectively. The activated carbon materials were characterized for their porous characteristics and elemental and proximate composition to examine their suitability as catalyst support. Catalysts were synthesized by supporting nickel on the activated carbon materials and tested for their performance in the methane dry reforming reaction. Microwave vacuum pyrolysis of PKS-derived char resulted in up to 89 wt% yield of activated carbon. The activated carbon was detected to have high Brunauer–Emmett–Teller (BET) surface area associated with a highly porous surface, characteristics of high adsorption capacity corresponding to many sites for adsorption of metal atoms with great potential for use as catalyst support material. Nickel atoms were detected on the surface of the activated carbon catalyst support, indicating successful synthesis of nickel-supported catalyst. The catalysts showed high methane conversion (up to 43 %), producing approximately 22 % gaseous products (CO + H2). These results show that activated carbon produced from microwave pyrolysis of palm kernel shell is a promising catalyst support material. Chemically activated carbon performed better as catalyst support compared with physically activated carbon in terms of CH4 and CO2 conversions.